PENGARUH DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP BELANJA DAERAH DI KABUPATEN PURWOREJO - Caecilia Rosma W (Politeknik Sawunggalih Aji, 2019)
The implementation of the regional autonomy policy is supported by the financial balance between the central government and regional governments as stated in Law No. 33 of 2004concerning Financial Balance between Central and Regional Governments. In the Act, what ismeant by the balance between the central and regional governments is the existence of agovernment financing system, which includes the financial division between the central andregional governments and regional distribution in a proportional, democratic, fair and transparentmanner by taking into account the potential, conditions and needs of each area. Equalization of inter-regional financial capabilities is intended to reduce capacityinequality between regions through the application of formulas that take into account regionalneeds and potential through the General Allocation Fund (DAU). In the implementation of regionalautonomy Regional Original Revenue (PAD) is also needed to provide flexibility to the regions inseeking funding as a manifestation of the principle of decentralization, as well as for the welfare ofthe people in the region, given the source of regional income received also has limitations. In carrying out efforts to increase the implementation of regional autonomy and the successof the decentralization system, it is necessary to analyze the General Allocation Fund (DAU) andRegional Original Revenue (PAD) on Regional Expenditures. This study aims to analyze thedominant income factors for regional spending, especially in Purworejo Regency for the period2010 to 2017. The results obtained are stated by the coefficient of determination value 0.966, which meansthat the general allocation fund and the original revenue area have a positive and significant effecton the regional expenditure with the contribution value of 96.6%. Partially, the general allocationfund has no effect on the regional expenditure and the original revenue of the region has an effecton the regional expenditure with a significance value of 0.006. Simultaneously, general allocationfund and local own revenue have positive and significant influence to local expenditure inPurworejo Regency with significance value 0.000.